A novel technique for Endobronchial Watanabe Spigot placement for bronchopleural fistula: a traction method. (19th July 2021) - Date, Naoki; Komatsu, Teruya; Fujinaga, Takuji
Abstract: Empyema with bronchopleural fistula is a challenging condition that often requires open-window thoracostomy. Bronchial occlusion with Endobronchial Watanabe Spigot is an effective and less invasive procedure to close the fistula; however, delivering a spigot into the target bronchus requires high technical skills. Herein, we report a case of bronchopleural fistula occluded with a spigot using a new 'traction method' in which the spigot is tied as an anchor to a guidewire and pulled into the target bronchus. Our method allows selective and steady placement of the spigot for patients who undergo open-window thoracostomy for the treatment of bronchopleural fistula.